The Effect of the Round-Robin Technique on Students' Vocabulary Mastery and Speaking Skills - Sondang Manik; Khairunnisa Br Malau; Ester Silitonga; Lastri W Manurung (South Sulawesi Education Development (SSED), 2024)
The objective of this research was to determine the vocabulary mastery and speaking skills of students after giving treatment by Round Robin technique, The researcher applied Round Robin Technique to solve vocabulary mastery and speaking skills in SMK AL Maksum Stabat. Round Robin is a technique that asks the student to be active in the learning process, Round Robin Technique involves the active participation of all group members. This technique is usually used to improve speaking skills and expand vocabulary. The researcher used a quasi-experimental design in this research, The total population was 86, The population consisted of two classes and every class consisted of 43 students, The sample of the research was taken by using a purposive sampling technique. The researcher did 6 meetings for oral tests, The experiment class was taught by the Round Robin technique and the control class was taught by the conventional technique. The researcher used tests before conducting the treatments, the researcher would give a test first to measure and analyze how far the students had. In this research, the researcher will use SPSS 25.05 to analyze the data using the Independent Sample T-test and the researcher get the result of the hypothesis showing that it was found Sig. of the t-test for equality of means assumed was 0.000 and α = 0.05. It means that Sig. (p-value) < α = 0.05. So, H0 was rejected and Ha was accepted, based on the data result of the test, it can be concluded that there was a significant effect of using the Round Robin technique in improving students’ vocabulary mastery and speaking skills in the first graders of SMK AL Maksum Stabat because there was an increase in students scores from before given the treatment and after given the treatment.